To design and fabricate of an innovative multipurpose hand truck / Muhammad Danish Dzulhelmy and Zeno Michael - Dzulhelmy, Muhammad Danish; Michael, Zeno (School of Mechanical Engineering, 2022)
In today’s life, people may have to transport many loads and objects of numerous quantities either at home or at work. There should be a utility that can help to carry the goods comfortably without forcing the user to apply more force. Using manual effort may cause injuries and fatalities of workers which is not a healthy work environment. This project is about designing and fabricating a Multipurpose Hand Truck. This project aimed to help manage loads without damaging the body and lower the risk of injury. Other than that, the purpose of this project is also to save money, time, and storage space. The steps taken to achieve this goal include sketching the product design, creating a CAD model of the design, and machining processes such as grinding, drilling and cutting by considering ergonomic factors so that the users can use it easily. The main material used to fabricate this product is steel because it has high strength characteristic which can carry heavy loads without any issues. This project has solved the difficulty that people were having with the existing hand trucks on the market. The project was completed successfully which can make the users feel comfortable and easier to use in daily life